Targeting ferroptosis for neuroprotection: potential therapeutic avenues in neurodegenerative and neuropsychiatric diseases - Khan, Muhammad S.; Hu, Qichan; Okeibunor, Kendrix; Ma, Liang; Bopassa, Jean C. (Frontiers in Physiology, 2025)
Ferroptosis is an iron-dependent programmed cell death that plays an important role in neurodegenerative and neuropsychiatric diseases. In the present study, we have highlighted how different risk factors are involved in the induction of ferroptosis in brain cells. In addition, we also demonstrated how ferroptosis plays an important role in different brain diseases. In our study why we focused and elaborated on the mechanisms of ferroptosis only in brain cells (Neurons, oligodendrocytes, and microglia) because they are particularly vulnerable to such kind of cell death. Additionally, brain cells are more dependent on mitochondrial function, iron regulation, and high levels of polyunsaturated fatty acids (PUFAs) as compared to peripheral body cells. Highlighting ferroptosis is more important because it has demonstrated several important mechanisms of neuronal injury and dysfunction which provides a deep understanding of the etiology of various brain diseases that were not sufficiently described by other programmed cell death pathways. Therefore, it has led to the exploration of new therapeutic strategies against various brain diseases and thus targeting ferroptosis-related proteins opens a new therapeutic window for several incurable brain diseases, and various ferroptosis regulators are now under clinical trials. However, their validation as a preclinical therapeutic agent is needed. Interestingly, here in our study we also summarize the most recent potential therapeutic targets and promising interventions which will provide a beam of light for future therapies against major brain diseases.